Targeted Therapies for Allergic Conjunctivitis: An Ophthalmologist's Perspective (Actualité en allergologie et en immunologie au Canada, 2023)
Allergic eye disease is extremely common as the eye is sensitive to irritants due to its constant exposure to the external environment. Approximately 40% of the general population is affected by ocular allergies. The majority of patients may also suffer with additional associated symptoms of allergic rhinitis, such as nasal congestion, sneeze, etc.; however, 6% may have isolated ocular symptoms. In addition, there are links between ocular allergies and other allergic conditions such as asthma, food allergy and atopic dermatitis. The challenge is that in addition to ocular symptoms, patients experience a substantial negative influence on their quality of life (QOL). The most common symptoms are watery and itchy eyes; redness; soreness; stinging; burning sensations; and swelling. Unfortunately, as these symptoms are quite common, most patients may choose to self-medicate and many cases are undiagnosed or underdiagnosed. As a result of this, patients may not utilize the correct management strategy; this can lead to a further propagation of symptoms and a greater reduction in patients’ QOL. Hence, it is crucial for patients to seek professional medical attention, while physicians must gather a comprehensive medical history and conduct relevant investigations. Additionally, the physician ought to propose the correct diagnosis and suitable treatment plan.